Fixed-line broadband: From ADSL to FTTH (2009)
This chapter will consider the structure of the fixed-line broadband market during the initial period of deployment, including observations based on econometric analysis. Fixed-line broadband began its explosive growth in Japan in 2001 when Softbank BB entered the market. Today, there are clear indications of a full-scale rollout of fiber to the home (FTTH) services, so it is widely believed that ADSL will be superseded by FTTH in the not-toodistant future. In this chapter I will consider fixed-line broadband from the following four points. First, citing data, I will examine the supply-side structure of fixed-line broadband. Taking up ADSL, FTTH, and CATV Internet in turn, I will examine trends in the number of subscribers, market shares, and price levels of each type of service. Second, I will consider the broadband user demand structure, based on a consumer questionnaire. I will examine peoples’ objectives in using the Internet, their reasons for selecting a particular service provider, and how and why they migrated from narrowband to broadband and from ADSL to FTTH Internet services. Third, I conduct a discrete choice model analysis based on the consumer questionnaire data. First, I will measure demand substitutability using actual revealed preferences (RP) data, focusing on the degree of price elasticity for the various services. Next, I consider the amount people claim they would be willing to pay for faster throughput using hypothetical choice situations and stated preferences (SP) data. Here, I focus on how the actual availability of FTTH affects consumers’ preferences. Fourth, I will address policy-related issues now under discussion including the definition of broadband markets, the state of effective competition in the ADSL market, and the degree of market dominance over the FTTH market.